Performance of crossbred pigs with indigenous and Hampshire inheritance under a smallholder production system in the Eastern Himalayan hill region - Kadirvel, Govindasamy; Devi, Yumkhaibam Sovarani; Naskar, Syamal; Bujarbaruah, K. M.; Khargariah, Gutum; Banik, Santanu; Singh, Ningthoujam Suraj; Gonmei, Chamniugongliu (Frontiers in Genetics, 2023)
Pig productivity is very low in Eastern Himalayan hill region due to the poor performance of nondescript pigs. To improve pig productivity, an objective was taken up to develop a crossbred pig with Niang Megha as indigenous and Hampshire as exotic germplasm. Performance of crossbred pigs with different levels of Hampshire and indigenous inheritance, viz., H-50×NM-50 (HN-50), H-75×NM-25 (HN-75) and H-87.5×NM-12.5 (HN-87.5) was compared for their performance to find suitable level of genetic inheritance. Among crossbreds, HN-75 performed better in terms of production and reproduction performance and adaptability. Inter-se mating and selection were carried out for six generations for HN-75 pigs and genetic gain and stability of the traits were evaluated and released as a crossbred. These crossbred pigs attained body weight of 77.5-90.7 kg by 10 months of age with FCR of 4.3:1. The age at puberty was 276.66±2.25 days and average birth weight was 0.92 ± 0.06 kg. The litter size at birth and weaning were 9.12±0.55 and 8.52±0.81. They have good mothering ability with a weaning percentage of 89.32±2.52 %, good carcass quality and consumer preference. The lifetime productivity for an average of six farrowing/sow showed total litter size at birth was 51.83±1.61 and total litter size at weaning was 47.17±2.69. At smallholder production system the crossbred pig showed better growth rate, higher litter size at birth and at weaning as compared to non-descript pigs. Hence, the popularisation of the crossbred would enhance the production and productivity, livelihood and income of the farmers in the region.